Why Zygon? The Journal's Original Visions and the Future of Religion-and-Science - Peters, Karl E. (Zygon, 2010)
Abstract. This essay briefly examines the original visions of Zygon, how they helped explain the publication of a new journal, and what they imply for where we might be going today.